KRITIK TERHADAP PANDANGAN SIGMUND FREUD: Agama dan Implikasinya terhadap Pendidikan - Abdul Rahman Barakatu (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
Freud considers that motivation source of religion behavior is sexual libido. He also states that religion is illusion, its adherent ails neurosis and childish, even he states that believing in God is useless action which handicaps the development of man per-sonality. Even though, he explains the analysis of super ego, but his opinion has implication which ignores the religion education such as adhered by the Western scholars, especially in 19 century. This case invites critics which asking the validity of Freud’s opinion and it is debated from point of view the use of methodology, philosophical thought by supporting empirical reality, and the content of Freud’s comment about religion.